İŞ İLİŞKİLERİNDE ÇATIŞMA VE SUÇ OLGUSU - TAN, SALMAN (Fırat Üniveristesi, 2007)
Günümüz toplumlarında; insanların, yaşamlarının büyük kısmını hayatlarını devam ettirmek için gerekli olan çalışma alanlarında geçirdikleri bilinmektedir. Sosyal bir varlık olarak insan, bu ortamlarda resmi olmanın yanı sıra gayri resmi anlamıyla da birçok ilişki türlerini bir arada yaşamaktadır. İster resmi, ister gayri resmi olsun iş ortamlarındaki bu ilişkiler bireyler arası çatışmalara da sebep olmaktadır. Bu durum suç olgusunu da beraberinde getirebilmektedir. İşte bu çalışmada iş ilişkilerinden kaynaklanan çatışma ve suç olgusuna farklı bir bakış açısı getirerek; mevcut durumu ortaya koyma amacı güdülmüştür

It has known that persons have spent most part of their lives in working places being necessary to survive in the life. In today?s society; it?s known that, humans have been living work areas which is necessary to go on their lives. Human beings as a social creative at the sometime man live together informal relation types as well as formal relation types in work place. It has caused conflicts among individuals both formal and informal levels in these workspace environment. Even if formal or informal these relations in work have a reason of conflict. These situations get into the crime together. So, in this study, conflict and crime, as a reason of the work relations and the present situation are aimed to be explained
Conflict and crime in work relations
Keywords: Sosyoloji